Differential Transform Method for Solving Volterra q-Integral Equations - Bhat, Altaf A.; Rizvi, Haider Abbas; Ganie, Javid A.; Sulaiman, Faiza A.; Jain, D. K. (Contemporary Mathematics, 2023)
In this paper, Volterra q-integral equations are solved by using the method of q-differential transformation. Exact solutions of linear and nonlinear q-integral equations have been investigated. To illustrate the method, several problems are discussed for the effectiveness and performance of the proposed method.